The impact of chronic kidney disease: experiences of patients and relatives from the extreme north of Brazil - Maria Virgínia Filgueiras de Assis Mello; Margareth Angelo (Universidad de Antioquia, 2018)
Objective. To identify the impact of chronic kidney disease on patients and their families. Method. This is a qualitative study conducted by the theoretical and methodological reference of Symbolic Interactionism and Narrative Research. The scenario of the study was the State of Amapá, in the extreme north of Brazil. Semi-structured interviews were conducted with 15 patients who experienced hemodialysis therapy and 16 family members. Results. The thematic analysis of the narratives resulted in the identification of two themes: life before the disease and life invaded by the disease. Conclusion. The diagnosis of chronic kidney disease and the need undergo hemodialysis emerged as a source of intense suffering, affecting the daily lives of the families as a whole and causing physical, psychological and social damages.   How to cite this article: Mello MVFA, Angelo M. The impact of chronic kidney disease: experiences of patients and relatives from the extreme North of Brazil. Invest. Educ. Enferm. 2018; 36(2):e02.